#TITLE_ALTERNATIVE# - SASONGKO (NIM 22198043); Pembimbing: Prof.Ir. Partanto Prodjosumarto, dan Dr.Ir. Irwandy Arif,, WAHYU
After discovering coal reserves by a company, then the problem is how to define the optimum net present value and how to design the. ultimate open pit limit. It depends on two important factors (1). coal reserves model (geologic and quality model) and (2). coal open pit economic model. Coal reserves model is then translating into mathematical model between strip ratio versus mineable reserves based on blocks model approach and contour lines total strip ratio called poligons. Coal open pit economic model, based on cash flows philosophy included interest, escalation of price and goverment financial payment, then translating too in the net present value optimisation model. As the case study of this thesis is in Pit 13B open pit mining of PT. Indominco Mandiri which operating at Sangatta, Kutai Timur district, East Kalimantan province. Based on the calculation by net present value optimisation model at coal price US$ 26/ ton, interest 12 %/year and escalation of price 3 %/ year, the result is : (1). If the production aim every year is variable : then the optimum net present value is : US $ 4,900,308, Government revenue US $ 10,636,827.22 recoverable coal reserves 2.842.875 ton at strip ratio 9,17 bcm/ton and mine age 4,50 years. Overburden which must be removed is 27.441.225 bcm and break even strip ratio is 12,92 bcm/ton. Th ultimate open pit limit lies between polygon PLGO8 and PLG09. (2). If the production aim every year is constant : 700.000 ton/year and, then the optimum net present value is : US$ 5,474,345, Government revenue US $ 11,001,869.44, recoverable coal reserves is 2.851.187.5 ton at strip ratio 9,19 bcm/ton and mine age 4,08 years. Overburden which must be removed is 27.581.487,5 bcm and break even strip ratio is 13,14 bcm/ton. The ultimate open pit limit lies between polygon PLGO8 and PLG09.